The utility of the musculocutaneous anterolateral thigh flap in pharyngolaryngeal reconstruction in the high‐risk patient. Issue 7 (14th February 2017) - Ooi, Adrian S.H.; Teven, Chad M.; Inbal, Amir; Chang, David W.
Abstract : BACKGROUND AND OBJECTIVES: Prior radiotherapy leads to increased wound complication rates for microsurgical reconstruction of pharyngolaryngeal (PL) defects. Incorporating vastus lateralis muscle together with anterolateral thigh flap (ALT) skin in defect reconstruction is useful in protecting vital structures and reinforcing irradiated neck skin and suture lines. This study shows the utility of the musculocutaneous ALT (MC ALT) in PL reconstruction in previously irradiated patients. METHODS: A single‐surgeon, retrospective chart review of all patients with defects of the PL region where an MC ALT was used for reconstruction from February 2014 to May 2016. The harvest of the MC ALT is described. RESULTS: Thirteen consecutive patients underwent reconstruction with a MC ALT flap. All 13 patients had received previous radiotherapy. PL defects included five partial, five subtotal, and three total. There was a 100% flap survival rate with five early recipient site complications including three fistulas, one neck abscess, and one partial muscle necrosis. Three patients (23%) developed strictures requiring dilatation, two of whom had received post‐reconstruction radiotherapy. CONCLUSIONS: The use of the MC ALT for reconstruction of PL defects should be considered to mitigate the negative effects of prior irradiation and provide a back‐up plan in instances where complications occur.